2013
DOI: 10.1590/s0102-311x2013000300010
|View full text |Cite
|
Sign up to set email alerts
|

Cobertura vacinal e fatores associados ao esquema vacinal básico incompleto aos 12 meses de idade, São Luís, Maranhão, Brasil, 2006

Abstract: O estudo objetivou avaliar a cobertura vacinal e os fatores associados ao esquema vacinal básico incompleto aos 12 meses de idade, em 427 crianças de 12 a 59 meses, em São Luís, Maranhão, Brasil, 2006. Trata-se de inquérito domiciliar transversal, de base populacional, com amostragem complexa por conglomerados. Empregou-se regressão de Poisson com ajuste robusto da variância. A cobertura para o esquema básico completo foi de 71,9% segundo doses aplicadas, 61,8% para doses válidas e 23,6% para doses corretas. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
2
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 21 publications
2
23
2
20
Order By: Relevance
“…Several studies have revealed lower parental education [10][11][12], lower income [10,13,14], mother's black skin color [10,15], extremes of mother's age, higher parity [16] and low number of prenatal visits [12] as barriers to complete immunization. More recent findings showed lower vaccination coverage in higher socioeconomic strata [9,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed lower parental education [10][11][12], lower income [10,13,14], mother's black skin color [10,15], extremes of mother's age, higher parity [16] and low number of prenatal visits [12] as barriers to complete immunization. More recent findings showed lower vaccination coverage in higher socioeconomic strata [9,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…22 In an ecological study, carried out with data referring to the municipality of Maringá, the veracity of the data on vaccination coverage in adults was questioned, emphasizing that they estimate little care for promotion and protection of health, among them the vaccination, 23 in addition to the lack of studies on the vaccination status in population groups other than children. 24 Thus, the need for strategies in the care practice and in research investigating the situation and vaccination coverage of the adult population, especially among men, is highlighted, which will allow, among other aspects, to identify social, economic and gender inequalities regarding the vaccination status. For this reason, the present study points to factors associated with the inadequate vaccination status of the adult male population, such as absence of partner and religion, and the unemployed occupational status.…”
Section: Discussionmentioning
confidence: 99%
“…Um inquérito domiciliar observou um gradiente diretamente proporcional entre cobertura vacinal e nível socioeconômico, com pior cobertura nos grupos mais vulneráveis socialmente (15). Dados de outro inquérito domiciliar apontam que crianças das classes econômicas menos favorecidas, sexo feminino e chefes de família de cor da pele preta, possuem percentuais mais elevados de esquema vacinal básico incompleto (16). Deve-se acrescentar, ainda, que quanto às vacinas não incluídas no esquema básico, as diferenças na cobertura vacinal entre os estratos socioeconômicos estão acentuadas, sendo que nos estratos socialmente menos favorecidos a cobertura é inferior a 3% (15).…”
Section: Entraves Para a Garantia Do Direito à Imunizaçãounclassified
“…As desigualdades socioeconômicas, raciais e de gênero configuram-se como barreiras à vacinação completa, o que indica a necessidade de fortalecimento das políticas equitativas que eliminem essas desigualdades, possibilitando coberturas vacinais que assegurem a todas as crianças e adolescentes proteção contra doenças imunopreveníveis (16).…”
Section: Desafios a Serem Enfrentados E Superadosunclassified